Pancreatic intraductal papillary mucinous neoplasm masquerading as ampullary adenoma: a diagnostic puzzle - Dellaportas, Dionysios (Ann Gastroenterol, 2020)
Intraductal papillary mucinous neoplasm (IPMN) is the most common pancreatic cystic lesion, remaining mostly asymptomatic. An atypical presentation of such a lesion, initially thought to be an ampullary adenoma, is presented herein. A 78-year-old white male with painless jaundice was treated in a tertiary hospital. Imaging and endoscopic investigations pointed towards an ampullary adenoma obstructing and causing dilatation of both bile and pancreatic ducts. Endoscopic papillectomy was carried out and histology revealed tubulovillous adenoma. Follow-up duodenoscopy 3 months later showed a recurrent lesion with mucous leaking from the pancreatic duct. Cytology revealed mucin-rich atypical cells, consistent with main-duct IPMN. Pancreatoduodenectomy was performed, finally revealing main-duct IPMN protruding through Vater’s ampulla. Cystic pancreatic lesions are increasingly found and IPMN is the most common of these. On the other hand, the management of ampullary adenomas has been revolutionized by endoscopic treatment and the advent of endoscopic papillectomy, with expanding indications. Meticulous clinical and imaging work up of these patients is essential to avoid suboptimal treatment. IPMN should be included in the differential diagnosis of ampullary adenomas, especially in the presence of a grossly dilated pancreatic duct.